Delayed presentation, diagnosis, and psychosocial aspects of male breast cancer. (13th March 2020) - Co, Michael; Lee, Andrea; Kwong, Ava
Abstract: Introduction: Male breast cancer is uncommon, delay in seeking medical attention often results in late presentation and poor prognosis. Methods: Retrospective review of a prospectively maintained database was performed. Patients who were still having regular follow‐up were contacted for telephone interview. Results: In this study, 56 male breast cancer patients were treated in our center from January 1998 to December 2018, accounting for 0.88% of all breast cancers treated during the same period of time. Median age of onset was 61 years old (Range: 33‐95). In this study, 6 (10.7%) patients presented with distant metastasis at the time of diagnosis and received palliative systemic treatment only. And, 50 patients were surgically treated and all had mastectomy. Axillary dissection was performed in 36 (72%) patients, while sentinel node biopsy was performed in 14 (28%) patients. Median tumor size was 23 mm (2‐100 mm). A Majority were diagnosed with invasive carcinoma (NOS), while 38 (67.8%) patients were node positive.Here 36 (64.3%) patients were alive at the time of the study, 31 (86.1%) patients responded to the telephone interview. More than 90% of our patients expressed various degrees of embarrassment at the time of breast symptom onset. Similarly, more than 90% of these patients experienced embarrassment while waiting in the breast center with predominant female patients. Most patients (N = 26) were not aware that breast cancer can occur in men prior to the diagnosis. Median duration from symptoms to the first medical consultation was 12.4 months (1‐120 months). Conclusion: Male breast cancer is rare and patients usually present late, Lack of knowledge, public education, and embarrassment are the important related factors. Abstract : Delayed presentation to medical care is common in male breast cancers, resulting in late presentation and poor prognosis. Reasons for the delayed presentation include lack of awareness of male breast cancer and embarrassment to feminine symptoms.